2008
DOI: 10.4048/jbc.2008.11.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns of Surgeons for the Management of Hereditary Breast Cancer in Korea

Abstract: . A total of 43 surgeons from 42 hospitals responded to the survey. Results: Of the respondents, 81.4% (n=35) asked for information related to the family histories of cancer and 58.1% (n=25) recommended genetic testing for their patients. Indications for genetic testing recommended by the 25 surgeons were the following: breast cancer patients with family histories of breast or ovarian cancer (96%), bilateral breast cancer (80%), early-onset (64%) or male breast cancer (52%), and a double primary malignancy wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…The first case of prophylactic mastectomy in Korea was a contralateral prophylactic mastectomy performed along with oophorectomy in 2008 [ 12 ]. However, prophylactic mastectomy is not routinely performed in Korea [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first case of prophylactic mastectomy in Korea was a contralateral prophylactic mastectomy performed along with oophorectomy in 2008 [ 12 ]. However, prophylactic mastectomy is not routinely performed in Korea [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, before the first phase of the KOHBRA study, a nationwide survey of 43 healthcare providers was conducted to examine practice patterns for the management of HBOC [30]. Among the respondents, 81.4% ascertained family histories of cancer and 58.1% recommended BRCA1/2 genetic testing for their patients at risk for HBOC.…”
Section: Genetic Counseling For Individuals At Risk For Hbocmentioning
confidence: 99%
“…This finding suggested that most Korean women with BRCA mutations chose intensive surveillance for cancer prevention. In addition, previous nationwide surveys of the management patterns of HBOC in 2007 and 2009 revealed the low uptake of chemoprevention and RRS for breast and ovarian cancer prevention in Korea [30,31]. …”
Section: Management Of Brca Mutation Carriersmentioning
confidence: 99%
“…When genetic counseling was conducted, it was carried out by the brea st surgeons themselves (81%) or by nurses (19%). 69) We conducted a follow-up survey 2 years after the initiation of the KOHBRA study. According to the 2009 follow-up survey, most physicians (60.0%) tended to draw a pedigree, which was higher than that reported in the initial 2007 survey (48.0%).…”
Section: ) Genetic Counseling In Koreamentioning
confidence: 99%